(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Market research is a critical component of the startup process, as it helps entrepreneurs understand their target market, competition, and potential risks. However, the depth of market research conducted by startups can vary greatly, leading to differing levels of success. This research paper aims to explore the causal relationship between market research depth and startup success rates. By examining existing literature, case studies, and surveys, this paper will analyze the impact of market research depth on various aspects of startup success, such as revenue growth, customer satisfaction, and investor funding. The findings of this paper can provide valuable insights for entrepreneurs and investors looking to improve their startup success rates through better market research practices.